Assessing the nonhuman primate reservoir of Schistosoma mansoni in Africa: a systematic review - Lindsay Richards; Berhanu Erko; Keerati Ponpetch; Sadie J. Ryan; Song Liang (BMC, 2019)
Abstract Background Reports of natural infections of Schistosoma mansoni in a number of species of nonhuman primates (NHPs) in Africa, coupled with the substantial overlap of NHP habitats and human schistosomiasis endemic areas, has led to concerns about the role of NHPs in the transmission of human schistosomiasis. We conducted a systematic review of the literature to describe the current scope of knowledge for Africa, for the NHP species implicated, their geographical distribution, infection rates with S. mansoni, and to discuss the implications for public health and conservation. Main text A systematic search of the literature was performed using PubMed, Web of Science, Google Scholar, the World Health Organization (WHO) library database, World Cat, and ScienceDirect without any language restriction. Studies examining S. mansoni infection of any African NHP species were included. Study types, primate species, their geographical distribution, and parasite diagnostic techniques reported in the studies were qualitatively summarized. Data for species with sample sizes ≥10 were included in the meta-analysis. We assessed the reported infection rate, and used a random-effects model to estimate the summary infection rates and 95% confidence intervals (CIs). We assessed heterogeneity among studies using the I 2 statistics. Twenty-nine publications, from 1960 to 2018, were identified and included in the review. The studies examined a total of 2962 primates belonging to 22 species in 11 genera across ten countries (Cameroon, Eritrea, Ethiopia, Gabon, Kenya, Nigeria, Senegal, Tanzania, Uganda, and Zimbabwe), and S. mansoni infections were found in nine species of five genera in all countries. When we excluded studies with sample sizes < 10, data from 24 studies on 11 species of primates in three genera in ten countries remained in the meta-analysis. The overall pooled estimate of infection rate was 10% (95% CI: 6-16%) with high heterogeneity (I 2 = 94.77%) across countries and species/genera. Among the three genera, Pan had the highest infection rate of 15% (95% CI: 0-55%), followed by Papio at 11% (95% CI: 6-18%), and Cercopithecus at 5% (95% CI: 0-14%). The association between NHP and human infections was positive, but not significant, due to low study sample matches and high variation. Conclusions Our findings suggest that S. mansoni infection rate is high in African NHPs, with substantial heterogeneities across species/genera and countries in Africa. Given the evidence for potential spillover and spillback of S. mansoni between African NHPs and humans, further research is urgently needed to understand ecology and mechanisms of transmission of the parasite between NHP and human hosts, in order to inform control strategies of this important neglected tropical disease.